Ramipril pretreatment worsened renal injury and survival despite a reduction in renal inflammation in experimentally induced sepsis in mice. (May 2020) - Bondeva, Tzvetanka; Schindler, Katrin; Schindler, Claudia; Wolf, Gunter
Introduction: The angiotensin converting enzyme inhibitor ramipril is a standard antihypertensive therapy for many patients. Because angiotensin II may promote inflammation, we were interested in whether basal pretreatment with ramipril may modify renal function and inflammation as well as systemic outcome in experimentally induced sepsis in mice. Material and methods: Ramipril (10 mg/kg/day) pretreatment or placebo (NaCl) was given intraperitoneally for 5 days to C57BL6/J mice, followed by either sham operation or cecal ligation and puncture sepsis induction. Real-time polymerase chain reaction and immunological stains were used to evaluate renal gene and protein expression, respectively. Plasma creatinine, neutrophil-gelatinase associated lipocalin, and blood urea nitrogen were used as markers for renal function. A clinical severity score was determined. Results: Administration of ramipril before cecal ligation and puncture surgery was associated with reduced renal inflammation but did not improved renal function and structure and even worsened the clinical status of septic mice. Conclusions: The data suggest that the effects of ramipril pretreatment are complex. Additional studies including monitoring of hemodynamic parameters are necessary to elucidate the exact mechanism(s) of this observation. In addition, the timing of the ramipril administration could be of importance.